Virtualization security:the good,the bad and the ugly - Yu-tao LIU; Hai-bo CHEN (网络与信息安全学报)
The virtualization security has increasingly drawn widespread attention with the spread of cloud computing in recent years.Thanks to another level of indirection,virtualization can provide stronger isolation mechanisms,as well as bottom-up security services for upper-level software.On the other side,the extra indirection brings complexity and overhead as well,which poses huge challenges.A series of recent representative work done by the institute of parallel and distributed system shanghai jiaotong university,including providing security services of trusted execution environment,virtual machine monitoring,intra-domain isolation,as well as optimizing trusted computing base and cross-world calls in the virtualization environment.Finally the problems and directions in the space of virtualization security were summarized.